Digital audio forensics - Tran, Duy Thien. (2011)
In the research field of Digital Audio Forensics, many researches have been done in Speech Recognition, Speaker Recognition, Audio Enhancement, but only a few can be found in Speaker Environment Recognition. This is due to the diversity of the environment, and the complexity to analyse it.